Hygroscopic Growth of Adsorbed Water Films on Smectite Clay Particles - Li, Xiaohan; Bourg, Ian C (Environmental science & technology, 2024)
Hygroscopic growth of adsorbed water films on clay particles underlies a number of environmental science questions, from the air quality and climate impacts of mineral dust aerosols to the hydrology and mechanics of unsaturated soils and sedimentary rocks. Here, we use molecular dynamics (MD) simulations to establish the relation between adsorbed water film thickness ( ) and relative humidity (RH) or disjoining pressure (Π), which has long been uncertain due to factors including sensitivity to particle shape, surface roughness, and aqueous chemistry. We present a new MD simulation approach that enables precise quantification of Π in films up to six water monolayers thick. We find that the hygroscopicity of phyllosilicate mineral surfaces increases in the order mica < K-smectite < Na-smectite. The relationship between Π and on clay surfaces follows a double exponential decay with e-folding lengths of 2.3 and 7.5 Å. The two decay length scales are attributed to hydration repulsion and osmotic phenomena in the electrical double layer (EDL) at the clay-water interface.